2014
DOI: 10.1016/j.preghy.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D status in Type 1 diabetic pregnancy: Impact on neonatal vitamin D status and association with maternal glycaemic control

Abstract: Objective: The first aim of this study was to assess 25-hydroxy vitamin D (25OHD) concentrations in women with type 1 diabetes (T1DM) during pregnancy, post-delivery and also foetal (cord blood) 25OHD concentrations and to examine relationships between these. The second aim of the study was to investigate potential interactions between maternal body mass index (BMI) and foetal vitamin D status. A further study aim was to examine potential relationships between maternal 25OHD and glycosylated haemoglobin (HbA 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“… Lipids were measured using a standard enzymatic colorimetric assay, and serum calcium, phosphate and albumin were measured using a photometric method on an automated Roche Cobas 8000 Modular system biochemical analyser (Roche Diagnostics, West Sussex, UK). Serum concentrations of 25‐OHD 2&3 were measured by means of liquid chromatography–tandem mass spectrometry (LC‐MS/MS) and results were presented as total 25‐OHD …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Lipids were measured using a standard enzymatic colorimetric assay, and serum calcium, phosphate and albumin were measured using a photometric method on an automated Roche Cobas 8000 Modular system biochemical analyser (Roche Diagnostics, West Sussex, UK). Serum concentrations of 25‐OHD 2&3 were measured by means of liquid chromatography–tandem mass spectrometry (LC‐MS/MS) and results were presented as total 25‐OHD …”
Section: Methodsmentioning
confidence: 99%
“…Serum concentrations of 25-OHD 2&3 were measured by means of liquid chromatography-tandem mass spectrometry (LC-MS/MS) and results were presented as total 25-OHD. 19…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Altogether, 12 studies were included in the analysis of the 25(OH)D levels in T1D patients . Table summarized the main studies and patients characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The potentially relevant references were identified by reviewing titles and/or abstracts, and/or full text of all citations identified with database searches. Out of 763 initial hits, 12 and 11 eligible studies were finally included in the metaanalysis of vitamin D levels in T1D and T2D patients, respectively. Ten studies were excluded for not providing exact standard deviation values of serum 25(OH)D levels in T1D or T2D patients .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, maternal vitamin D deficiency may also increase the risk of T1D in off-springs [32]. It has been suggested that vitamin D may contribute to immune modulation and thereby protect or arrest an ongoing immune activations [31].…”
mentioning
confidence: 99%